Effect of Priming on Seed Viability and Vigour in Cashew (Anacardium occidentale L.) - C. MINI; JOSE MATHEW (Seed Research, 2026)
Study conducted at Cashew Research Station, Madakkathara under Kerala Agricultural University, India during 2003 and 2004 to explore the possibility of extending the storage life of cashew seeds by priming with various chemicals and growth regulators. It was found that priming of cashew seeds results in extension of seed viability. Untreated seeds and seeds soaked in water for 12 hours were always inferior and exhibited poor germination percentage and vigour index. Cashew seeds could be stored up to 13 months with more than 70 per cent germination and up to 17 months with 60 per cent germination by priming after one month of storage with thio urea 5000 ppm for 24 hours at ambient temperature.